Development of a Double-Skin Façade for Sustainable Renovation of Old Residential Buildings. Issue 1 (February 2013) - Kim, Gon; Schaefer, Laura; Kim, Jeong Tai
The modernist movement in architecture has led to a building boom of a large number of high-rise buildings with glazed façades. These façades were aesthetically pleasing, but have a high energy loading. To address this, a double-skin façade (DSF) has been proposed to manage the interaction between the outdoor and indoor environments. A DSF can contribute to balance the demand for energy saving, thermal and visual comfort, and a high-tech image for building envelopes. The design of the DSF involves decisions on geometric parameters, glass selection, ventilation strategy, shading, daylighting, aesthetics, wind loads, and maintenance and cleaning cost expectations. This paper reports an experimental application of a DSF in an old apartment building which has been modelled in order to find the configuration to select design parameters that could minimize the energy demand and total carbon emissions. A simulation-based virtual environment program was used to determine the optimal sustainable features of the double-skin envelope. Results of the simulation are presented and discussed for four different cavity widths and ventilation modes of operation, highlighting the potential savings in comparison to the existing façade construction. The impact of internal shading within cavity space was also investigated.